Peptidase Inhibitor 15 (PI15) Regulates Chlamydial CPAF Activity - Prusty, Bhupesh K.; Chowdhury, Suvagata R.; Gulve, Nitish; Rudel, Thomas (Frontiers in Cellular and Infection Microbiology, 2018)
Obligate intracellular pathogenic Chlamydia trachomatis express several serine proteases whose roles in chlamydial development and pathogenicity are not completely understood. The chlamydial protease CPAF is expressed during the replicative phase of the chlamydial developmental cycle and is secreted into the lumen of the Chlamydia-containing vacuole called inclusion. How the secreted protease is activated in the inclusion lumen is currently not fully understood. We have identified human serine peptidase inhibitor PI15 as a potential host factor involved in the regulation of CPAF activation. Silencing expression as well as over expression of PI15 affected normal development of Chlamydia. PI15 was transported into the chlamydial inclusion lumen where it co-localized with CPAF aggregates. We show that PI15 binds to the CPAF zymogen which may support CPAF protease activation at low concentrations. However, at high concentrations PI15 inhibits CPAF activity possibly by blocking its protease domain. Our findings shed light on a new aspect of chlamydial host co-evolution which involves the recruitment of host cell proteins into the inclusion to control the activation of bacterial proteases like CPAF that are important for the normal development of Chlamydia.